THE ROLE OF ISLAMIC ART IN ENHANCING THE SPIRITUALITY OF INDONESIAN YOUNG GENERATION - Rohmad, Muhammad Ali (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2020)
Islamic art is radiant beauty of the Islamic spiritual. The young generation must be able to be the front guard in preaching a beautiful religion. The public abandoned Islamic art because it was considered ancient and inferior to the conventional art, which was increasingly innovative. But lately, Islamic art has become popular in Indonesian people again as a phenomenon which is widely discussed, namely the pesantren literary art, represented by the novel Hati Suhita by Khima Anis. While, Islamic music art represented by Sabyan Gambus. As long as Islamic art can maintain quality and continue to innovate, Islamic art can break the dominance of conventional art in Indonesia. With the increasing interest of young people towards Islamic art, of course, it will increase their spirituality.